2022
DOI: 10.3389/fvets.2022.851865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Anemoside B4 on Diarrhea Incidence, Serum Indices, and Fecal Microbial of Suckling Calves

Abstract: The study was conducted to evaluate the effects of Anemoside B4 on diarrhea incidence, serum indices, and fecal microbial of suckling calves. Sixty newborn Chinese Holstein calves with similar body weight (43.7 ± 3.9 kg) were randomly divided into four groups with 15 calves each, fed the diet which was supplied 0 (CON), 15 (A1), 30 (A2), and 45 (A3) mg/day of Anemoside B4, respectively. The trial period is 56 days. The blood and fecal samples were collected at 28 and 56 days of age. Results show that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…(Gee et al, 1997). The addition of Anemoside B4 could significantly reduce diarrhea incidence in suckling calves at 14-28 days and promote the digestibility and metabolic rate of total energy and had no adverse effect on the rumen fermentation index of calves (Lu et al, 2023). The effects of bitter melon saponins diets have adverse effects on intestinal digestion with the supplemental level of 6,400 mg/kg in Songpu mirror carps (Fan et al, 2023).…”
Section: Alfalfa Saponins On Nutrient Digestibility Daily Gain and Di...mentioning
confidence: 98%
See 1 more Smart Citation
“…(Gee et al, 1997). The addition of Anemoside B4 could significantly reduce diarrhea incidence in suckling calves at 14-28 days and promote the digestibility and metabolic rate of total energy and had no adverse effect on the rumen fermentation index of calves (Lu et al, 2023). The effects of bitter melon saponins diets have adverse effects on intestinal digestion with the supplemental level of 6,400 mg/kg in Songpu mirror carps (Fan et al, 2023).…”
Section: Alfalfa Saponins On Nutrient Digestibility Daily Gain and Di...mentioning
confidence: 98%
“…Some early studies have shown that some kinds of saponins were related to ruminant abdominal distension (Lindahl et al, 1957;; however, recent research has shown that saponins are composed of one additional factor in the pathogenesis of herbage inflation (Hristov et al, 1999;Santoso et al, 2004;Lin et al, 2020;Lu et al, 2023). Yucca saponin and Panax quinquefolium saponin have several current and potential applications in animal nutrition and their effects on pig performance are Effects of Dietary Alfalfa Saponin on Digestive Physiology in Weaned Piglets well-conducted (Makkar et al, 1998;Hristov et al, 1999;Santoso et al, 2004).…”
Section: Introductionmentioning
confidence: 99%